Different sectoral land use policies: Implications of Decentralization and Urban Planning on Flooding in Freetown. - Bankolay Theodore (African Journal on Land Policy and Geospatial Sciences, 2024)
ABSTRACT Context and background : the relationship between urbanization, climate change, and flooding has been a focal point of academic and policy discourse. while the impacts of climate change on precipitation patterns and sea-level rise are increasingly recognized,the role of urban planning and governance in exacerbating flood risks remains a subject of debate. studies have primarily focused on developed countries, with limited research on the specific challenges faced by rapidly urbanizing cities in developing regions like Freetown in west africa. Goal and objectives: The study aims to investigate the complex interplay between decentralization, urban planning, and flooding in Freetown, Sierra Leone. By examining the effectiveness of current policies and governance structures, the research seeks to identify key factors contributing to the city's vulnerability to flooding and propose evidence-based recommendations for mitigation and adaptation. Methodology: a cross-sectional research design was employed to collect both quantitative and qualitative data. quantitative data were analyzed descriptively to identify patterns and trends in flooding occurrences, while qualitative data were subjected to content analysis to explore the perceptions of stakeholders and policymakers regarding the causes and consequences of flooding. Results: The findings reveal that inefficient and ineffective decentralization of governance functions to the Freetown city council, stemming from a lack of political will and leadership, has hindered effective flood management. The absence of strong and harmonious spatial planning has exacerbated uncontrolled urban sprawl, leading to increased pressure on infrastructure and environmental degradation.